Proceedings of the 1st Aceh Global Conference (AGC 2018) 2019
DOI: 10.2991/agc-18.2019.84
|View full text |Cite
|
Sign up to set email alerts
|

Do Fiscal Decentralization and Human Development Index Affect Poverty in Indonesia?

Abstract: The study aim is to analyze how the effects of fiscal decentralization and Human Development Index (HDI) on poverty in Indonesia. This study employ secondary data in the form of time series from 2010 to 2017, and cross section data consisting of 33 provinces in Indonesia, so that the type of polled data can be categorized that is a combination of time series data (for 8 years) with cross section data 33 Province in Indonesia. The analytical method used is PLS (Panel Least Square) with a comparison of two model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Human Development Index—HDI is an index proposed by the UNDP to measure well‐being of the people of a country worldwide (Gaye, 2011; Ghislandi et al, 2018; Graafland, 2019; Isaac et al, 2021; Khodabakhshi, 2011; Mazzanti et al, 2020; Mwabukojo, 2019; Ofosu‐Mensah Ababio et al, 2020; Soondram et al, 2022; Talaber, 2006; United Nations, 2007; Varlitya et al, 2018). Human Development Index is a very useful measure for international comparison between countries in respect of people's welfare (Perez & Claveria, 2020; Ülengin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Human Development Index—HDI is an index proposed by the UNDP to measure well‐being of the people of a country worldwide (Gaye, 2011; Ghislandi et al, 2018; Graafland, 2019; Isaac et al, 2021; Khodabakhshi, 2011; Mazzanti et al, 2020; Mwabukojo, 2019; Ofosu‐Mensah Ababio et al, 2020; Soondram et al, 2022; Talaber, 2006; United Nations, 2007; Varlitya et al, 2018). Human Development Index is a very useful measure for international comparison between countries in respect of people's welfare (Perez & Claveria, 2020; Ülengin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies on socio‐economics identified longevity, knowledge, and income inequality as the major components of the Human Development Index (Avik & Sengupta, 2019; Batrancea et al, 2018; Etim et al, 2020; Ghislandi et al, 2018; Mukherjee et al, 2014; Raghupathi & Raghupathi, 2020; Sehrawat & Giri, 2014; Ülengin et al, 2011; Varlitya et al, 2018; Yang & Mukhopadhaya, 2019; to mention few). The 2018 UNDP report reiterated that the HDI combines health, education, and income information in one number to express human progress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations